Practical Group Defense Exercise Design in Football Game for 13-Year-Old Students - Ihsan, Nurul; Okilanda, Ardo; Donie, Donie; Putra, Dede Dwiansyah; Wanto, Sugar; Arisman, Arisman (Physical Education Theory and Methodology, 2022)
Research purpose. Football is popular in the society across the world. Everyone always watches football matches. Nowadays, there are many football schools for kids or young athletes. Thus, there is a need for a model of exercise that is appropriate for young athletes. This study aimed to create a model of group defense exercise in a football game. It referred to 13-year-old football school students. It was designed using psychological and physiological characteristics of the 13-year-old. Materials and methods. The study participants were 120 football players aged 12 to 13. The study used a research and development method (R&D) through Borg and Gall model. Data was obtained from observation, interview and questionnaires. Data analysis techniques used expert judgments and three steps from Miles and Huberman, namely reduction of data, display of data, and making conclusions. Results. The findings show that the model of defense exercise in football for a 13-year-old football school player has 13 variations of the exercise. It was created based upon the psychological and physiological characteristics of a young player. Conclusions. The result of the study is a recommendation for teachers or coaches to improve the defense exercise in football as player needs.